Toward a new theory of exploitation. A dialogue with Nancy Fraser - Mezzadra, Sandro (Scenari, 2023)
The essay discusses Nancy Fraser’s work taking as a point of departure her famous controversy with Axel Honneth on redistribution and/vs. recognition. The way in which Fraser frames gender and race in that controversy is taken as a guiding thread for the analysis of her writings on the relation between sexism, racism, and capitalism in the following years. Race and gender have been key to the plea that the very notion of capitalism needs to be expanded, in particular to include social reproduction. Fraser’s contribution to feminist debates over the last years is discussed from this angle, emphasizing her attempt to combine Marx and Polanyi to forge a critical theory of capitalism up to the challenges of the present. The essay ends with an analysis of the important distinction proposed by Fraser between the concepts of expropriation and exploitation. A critique of the narrow way in which the latter is understood and an attempt to outline an expanded theory of exploitation conclude the essay.